Toward sustainable waste management: assessing the potential implications of Sabah's Solid Waste and Public Cleansing Management Enactment 2022 - Dusim, Haidy Henry (Faculty of Administrative Science and Policy Studies, 2025)
The Solid Waste and Public Cleansing Management Enactment 2022 marks a legislative milestone for sustainable waste management in Sabah. This study applies document analysis to assess its potential impacts, focusing on institutional frameworks, waste minimization strategies, financial mechanisms, and enforcement provisions. Unlike previous research that mainly described Malaysia’s federal legislation, this paper highlights how the Enactment offers a state-driven model tailored to Sabah’s local governance context. The findings suggest that while the Enactment has strong potential to strengthen institutional clarity and funding mechanisms, its success will depend on overcoming challenges such as limited municipal budgets, enforcement capacity, and public participation. This study contributes to policy discourse by situating Sabah’s approach within broader Southeast Asian waste governance trends. Limitations include reliance on documentary sources; future studies should incorporate stakeholder interviews to deepen practical insights.